Outcome of the public consultation on the draft administrative guidance on the preparation and presentation of applications for authorisation of additives for use in animal nutrition. Issue 4 (9th April 2019) - ,
Abstract : The European Food Safety Authority (EFSA) carried out a public consultation to receive input from the scientific community and all interested parties on the draft administrative guidance on the preparation and presentation of applications for authorisation of additives for use in animal nutrition (update 2019) prepared by the EFSA Applications Desk Unit to support applicants in preparing applications for authorisation of feed additive. The written public consultation for this document was open from 21 November to 12 December 2018. EFSA received a total of 70 comments from eight interested parties. EFSA wishes to thank all stakeholders for their contributions. The current report summarises the outcome of the public consultation, and includes all the comments received and how the comments were addressed. The Applications Desk Unit prepared an updated version of the guidance document taking into account the questions and comments received. This guidance was finalised on 22 March 2019 and is published on the EFSA website. Abstract : This publication is linked to the following EFSA Journal article: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2007.1447/full